CeO2 nanoparticles induce no changes in phenanthrene toxicity to the soil organisms Porcellionides pruinosus and Folsomia candida - Tourinho, Paula S.
Cerium oxide nanoparticles (CeO2 NPs) are used as diesel fuel additives to catalyze oxidation. Phenanthrene is a major component of diesel exhaust particles and one of the most common pollutants in the environment. This study aimed at determining the effect of CeO2 NPs on the toxicity of phenanthrene in Lufa 2.2 standard soil for the isopod Porcellionides pruinosus and the springtail Folsomia candida. Toxicity tests were performed in the presence of CeO2 concentrations of 10, 100 or 1000 mg Ce/kg dry soil and compared with results in the absence of CeO2 NPs. CeO2 NPs had no adverse effects on isopod survival and growth or springtail survival and reproduction. For the isopods, LC50s for the effect of phenanthrene ranged from 110 to 143 mg/kg dry soil, and EC50s from 17.6 to 31.6 mg/kg dry soil. For the springtails, LC50s ranged between 61.5 and 88.3 mg/kg dry soil and EC50s from 52.2 to 76.7 mg/kg dry soil. From this study it may be concluded that CeO2 NPs have a low toxicity and do not affect toxicity of phenanthrene to isopods and springtails.